Study of Microorganisms’ Viability and Integrity of Structural Sites of Their DNA, Amplified in PCR After Low-Temperature Storage under Different Conditions - Vysekantsev, I. P.; Omelchenko, E. A.; Gurina, T. M. (Problems of Cryobiology and Cryomedicine, 2003)
The obtained experimental data testify to the fact that under low temperature preservation the cyclic changes in storage temperature from –196 to –100°C can result in additional death of microbial cells. In microbial cells, stored under liquid nitrogen constant temperature and under conditions of storage temperature variation within the mentioned range, there are preserved the DNA structural sites, providing the amplification in polymerase chain reaction (PCR) of specific fragments.